(untitled) (Anais do Congresso Brasileiro de Processo Coletivo e Cidadania, 2022)
The present work intends to be a critical analysis and a doctrinal and jurisprudential survey to deal with the judicialization of reproductive public policies and the limitations imposed by the public budget. It is an exploratory study that used bibliographical, documentary, quantitative and qualitative research to analyze the (de)regulation of assisted human reproduction in Brazil, through a critical perspective on the role of the Judiciary as a supposed promoter of unattended social rights by the executive body, which often fails to devise and implement efficient public policies. In this sense, it is analyzed whether, when entering the sphere of action of the executive and legislative powers, judicially granting the citizen the reproductive right not reached by the public policy previously idealized, the judge would be reaffirming social rights or denying the same rights to the community.